PENATALAKSANAAN ENDOMETRIOSIS - Suparman, Erna (UNIVERSITAS SAM RATULANGI, 2012)
Abstract: Endometriosis is characterized by the occurence of endometrial cells outside the uterine cavity. Endometrial tissue in the pelvic cavity increases the activity of macrophages to phagocyte endometrial tissue debris and influences intrauterine implantation. Bleeding, arising from endometriosis lesions, will lead to adhesions with surrounding tissues, resulting in changes of tubal motility, pain, and infertility. Laparoscopy examination is necessary for confirming the diagnosis. While transvaginal ultrasound is famous for its accuracy, it provides just a little help for finding cystic masses in the parametrium. Nowadays, the treatment of endometriosis with estrogen is begining to be abandoned because it may cause endometrial hyperplasia that can develop into endometrial cancer. Albeit, danazol treatment succeeds due to its hormonal and immunologic effects. The first-line of therapy given for reducing pelvic pain is NSAIDs or oral contraceptives. If this fails, a GnRH agonist is given in combination with estrogen and progestin as an add-back therapy, otherwise an operative laparoscopy has to be done. Concerning the degree of severe and extensive endometriosis, atraumatic surgery is the main option. The induction of ovulation shows a satisfactory result. Randomized trials using the GnRH agonist administration associated with the hormones (FSH and LH), clomiphene citrate, and intrauterine insemination, showed an increased incidence of pregnancy compared to those without therapy.Key words: endometriosis, hormones, pain, infertilityAbstrak: Endometriosis ditandai adanya sel-sel endometrium di luar kavum uteri. Jaringan endometrium di dalam rongga pelvis akan meningkatkan aktifitas makrofag untuk memfagositosis debris jaringan endometriosis serta mempengaruhi nidasi intrauterin. Perdarahan yang timbul dari lesi endometriosis akan menyebabkan perlekatan dengan jaringan sekitarnya, yang berakibat perubahan motilitas tuba, nyeri, dan infertilitas. Laparoskopi sangat diperlukan untuk diagnosis endometriosis. USG transvaginal yang tersohor karena akurasinya hanya sedikit membantu menemukan lesi di daerah parametrium. Dewasa ini, pengobatan endometriosis dengan estrogen mulai ditinggalkan karena mengakibatkan hiperplasia endometrium yang dapat berkembang menjadi kanker endometrium. Keberhasilan pengobatan dengan danazol disebabkan karena efek hormonal dan imunologiknya. Terapi lini pertama pada nyeri pelvis ialah NSAID atau kontrasepsi oral. Bila gagal, diberikan agonis GnRH dikombinasi dengan estrogen dan progestin add-back therapy, atau laparoskopi operatif. Pada endometriosis derajat berat dan luas, pembedahan atraumatik merupakan pilihan utama. Induksi ovulasi memberikan hasil yang cukup memuaskan. Randomized trials pada pemberian GnRH agonis dengan hormon FSH dan LH, clomifen sitrat, serta inseminasi intrauterin, memperlihatkan peningkatan angka kehamilan dibandingkan pada yang tanpa terapi.Kata kunci: endometriosis, hormon, nyeri, infertilitas